The Effects of Beliefs and Health Literacy on Medication Use in Culturally And Linguistically Diverse Populations: A literature review - Ebuka-Olisaemeka Nwafor; Julie Stevens; Sarah Hosking; Eman Rafhi; Joon Soo Park; Sang-Woon Jeon; Kate Wang (Asia Pacific Journal of Health Management)
Social and individual factors (beliefs, and health literacy) play a crucial role in health promotion and disease prevention among older culturally and linguistically diverse (CALD) populations. This review examines the recent publications regarding the impact of health beliefs, and health literacy on patients' medication use involving adherence, polypharmacy, and potentially inappropriate medications (PIMs) in older CALD population.